Educação ambiental: ações compartilhadas na escola e na comunidade - Azevedo, Carla Juny Soares de (2002)
The activities told here are connected to a proposal of Environmental Education (EA) backed theoretical and methodology in the investigation-action emancipator and in the “Freireana” conception. In the proposal of the investigation-action the searching interact with the social subjects of the context investigated by means of the dialogue. It is recognized as essential the articulation among the school knowledge, the community's existence and those embraced starting from the technicians' of different government and no-government institutions approach, as middle of supplying the necessary support to the community organization so it can demand better life conditions and its right to the access the urban land. It is therefore, of a research project, teaching and extension, committed with the social subject that looks for to build to a do collaborator in the pedagogic practices and in the community actions, trying to deepen the communication of the school with the community. This project involves a proposal of collective planning of the activities curriculum, of which you/they teachers participate and students of the (Preschool to 4ª series of the Fundamental Teaching) of the School of Municipal Fundamental Teaching Sao Paulo (EMSP). This he/she interferes in a community that presents groups or collectives, seated in public areas lacking services of urban infrastructure, as the basic sanitation among others. From among the results can stand out the integration to the project, of the Municipal School of Teaching Infantile Russian Mountain, that he/she also assists that community, with the incorporation of more a mastership proposal. The formation of an investigative group and composed collaborator for women and Vila N.S'S community's inhabitants. Aparecida, from where they come approximately, 90% of the students of the school. The Group has been trying to organize the community to discuss its priorities. It organized partnerships for accomplishment of the inhabitants' register, whose dwellings until the present, inexistent for the Municipal Public Power. It not just participated of the application, but it collaborates with the analysis of the same. In almost 40 years of existence of the Villa, only on this year, the inhabitants got that it was implanted the collection of the garbage, result of the fight that comes undertaking in direction to the inhabitants' mobilization, to the articulation of partnerships and the to vindicate before the Public Power.